2011
DOI: 10.4081/ija.2011.6.s1.e3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the GAEC cross-compliance standard Short-term measures for runoff water control on sloping land (temporary ditches and grass strips) in controlling soil erosion

Abstract: The agronomic measures made obligatory by the cross-compliance Standard Temporary measures for runoff water control on sloping land included in the Ministry of Agricultural, Food and Forestry Policies (MiPAAF) decree on cross compliance until 2008, and by Standard 1.1 Creation of temporary ditches for the prevention of soil erosion in the 2009 decree, certainly appear to be useful for the control of soil erosion and runoff. The efficacy of temporary drainage ditches and of grass strips in controlling runoff an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Therefore, the present soil distribution reflects past farming practices, intensive exploitation of soils and monoculture, improper forest management, and abandonment of soil set-up systems which have initiated land degradation in many regions (Piccarreta et al, 2006;Corti et al, 2013). Particularly in the widespread mountainous environments, which includes many Italian regions, the mechanization has triggered erosion processes (Bazzoffi and Jakab, 2006;Bazzoffi et al, 2011), producing heavy soil losses and reducing the thickness of the solum. Erosion has consequently induced a slow process of pedogenetic involution that has transformed previous soils into Entisols, i.e.…”
Section: Reviewmentioning
confidence: 99%
“…Therefore, the present soil distribution reflects past farming practices, intensive exploitation of soils and monoculture, improper forest management, and abandonment of soil set-up systems which have initiated land degradation in many regions (Piccarreta et al, 2006;Corti et al, 2013). Particularly in the widespread mountainous environments, which includes many Italian regions, the mechanization has triggered erosion processes (Bazzoffi and Jakab, 2006;Bazzoffi et al, 2011), producing heavy soil losses and reducing the thickness of the solum. Erosion has consequently induced a slow process of pedogenetic involution that has transformed previous soils into Entisols, i.e.…”
Section: Reviewmentioning
confidence: 99%
“…In un precedente lavoro, realizzato nel progetto EFFICOND (Bazzoffi et al, 2011), il modello RUSLE è stato applicato nella valutazione comparativa del rischio di erosione su aree campione in presenza o in assenza dei solchi acquai, così come prescritti dalla Norma 1.1(impegno a).…”
Section: Applicazione Del Modello Rusle In 60 Aree Del Controllo Ageaunclassified
“…These changes also occurred in Tuscany from 1950s, where agricultural mechanization has led to an expansion of the field size and reduction of ditching, terracing, tile draining and channelization to make machine operation more feasible and cheaper, but negatively affecting the drainage effectiveness (Landi, 1989;Napoli and Orlandini, 2015;Napoli et al, 2016). As a consequence, these transformations have made sloping fields less resilient to storms and accelerated the soil erosion processes (Borselli et al, 2006;Bazzoffi et al, 2011Bazzoffi et al, , 2016Tarolli et al, 2014). Nowadays, several studies indicated water erosion as one of the most important soil degradation processes, resulting in a reduction of soil fertility and long-term productivity (Lal, 1995;Gunatilake and Vieth, 2000;Ramos and Martínez-Casasnovas, 2006;Pulighe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%